Malandragem e cidadania: novas pistas - Souza, Venceslau Alves de (2008)
This study was written from a nonIberian perspective to analyze a phenomenon that is very wellknown in Brazil and which is commonly referred to as malandragem . This social practice is examined from the point of view of a theory of social action, in other words, from the starting point of a Western way of thinking that is in opposition to theories that seek its existence in premodern emotionThis study argues that malandragem is much more a product of our modernity, that has been evident since the beginning of the nineteenth century particularly in the resistance of the dominated groups in society which resulted in the formation of the malandro , malandragem , and manifestations such as the jeitinho (Brazilian way), xaveco (flirting), ginga (swing), darse bem (to do well ) levar vantagem ( to take advantage ) jogo de cintura ( to know how to deal with situations). It is also in that resistance that by allowing malandragem to be accepted as a national characteristic it is possible to hide the latent conflict behind the modern forms of domination that (paradoxically) allow human rights to be advanced. The domination is also accentuated in the interclass relationship which distances those individuals from those rights and moves them closer to malandragem